The Impact Of Exchange Rate, Inflation And Interest Rates On Indonesian Mining Product Exports - Arsyaf Tampubolon; Amin Hou; Dwita Sakuntala (Jurnal Ekonomi, 2024)
Exports of mining products generate substantial state revenue through export duties and taxes. This income can be used to finance national development in various fields such as infrastructure, education and health. Apart from that, mining products contribute to strengthening Indonesia's foreign exchange reserves, which in turn helps maintain macroeconomic stability. This research was conducted to analyze factors that could influence the growth of exports of Indonesian mining products. The dependent variable used in this research is the value of mining exports and the dependent variables are the dollar exchange rate, inflation rate and interest rates. The research was conducted in Indonesia with data taken for the period from 2010 to 2023. The data sources used were secondary data obtained from the Indonesian Central Bureau of Statistics and Bank Indonesia. Data analysis uses the help of e-views software by carrying out multiple regression analysis tests. The results of this research prove that inflation and interest rate variables influence exports of Indonesian mining products. The exchange rate has no effect on exports of mining products in Indonesia.